KONSEKUENSI YURIDIS PUTUSAN MAKAMAH KONSTITUSI NO. 46/PUU-VIII/2010 TERHADAP KEDUDUKAN ANAK ASTRA DALAM HUKUM ADAT BALI - Pramana, I Gede Pasek (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
This research aims to analyze about the significance of the Constitutional Court Decision No.46/PUU-VIII/2010 the position of anak astra in Bali customary law. The research method used is a normative study by selecting the type of statue approach and the conceptual approach. Sources of legal materials that were examined in this study consisted of primary legal materials and secondary legal materials and techniques were analyzed with the description, systematic, evaluation and argumentation. Based on the perspective ( review ) Constitutional Court Decision No. 46/PUU-VIII/2010, anak astra have a civil relationship with her biological father and his family along can be proved by science and technology and / or other evidence according to the law. The juridical consequences of the Constitutional Court Decision No. 46/PUU-VIII/2010 to the norms of Bali customary law about anak astra Bali is must conform to the directions of law in the Decision of the Constitutional Court.
Keywords: Anak astra; Constitutional Court Decision No. 46/PUU-VIII/2010; Legal Position